Computation and Analysis of Highly Stable and Efficient Non-toxic Perovskite CsSnGeI3 Based Solar Cells to Enhance Efficiency Using SCAPS-1D Software - Hossain, Md Momin; Khan, Md Yakub Ali; Halim, Md Abdul; Elme, Nafisa Sultana; Islam, Md Shoriful (Association for Scientific Computing Electrical and Engineering (ASCEE), 2023)
This paper examines the physical, optical, and electrical characteristics of cesium tin-germanium triiodide based single halide Perovskite absorption materials in order to provide the best photovoltaic application. In light of the diversification of the use of natural resources, perovskite solar cells are becoming more and more essential for capturing renewable energy. In this research work, a cesium tin–germanium triiodide (CsSnGeI3) perovskite-based solar cell (PSC) has been reported to achieve a high-power-conversion efficiency (PCE). CsSnGeI3 perovskite-based solar cell has been proposed for the Pb and toxic-free (Al/FTO/ TiO2/CsSnGeI3/Mo) structure simulated in Solar Cell Capacitance Simulator (SCAPS-1D software. At first aluminum, fluorine-doped tin oxide, Titanium dioxide, cesium tin–germanium triiodide and Molybdenum have been inserted into SCAPS and simulated using specific temperature. In this simulation, the electron transport layer (ETL) FTO, the buffer layer TiO2, and the absorber layer CsSnGeI3 were all used. Utilizing variations in thickness including absorber and buffer, defect density, operating temperature, back contact work function, series and shunt resistances, acceptor density, and donor density, the performance of the proposed photovoltaic devices was quantitatively assessed. Throughout the simulation, the absorber layer thickness was held constant at 1.6 ?m, the buffer layer at 0.05 ?m, and the electron transport layer at 0.5 ?m. A solar cell efficiency of 24.75%, an open-circuit voltage of 0.95 volts, a short-circuit current density of 30.61 mA/cm2, and a fill factor (FF) of 85.42% have all been recorded for the CsSnGeI3 absorber layer. Our ground-breaking findings unequivocally show that CsSnGeI3-based PSC is a strong contender to quickly overtake other single-junction solar cell technologies as the most effective.